Illustrated Stories against Online Gambling - Falah Anargya Setia Nusabela; Vina Mahdalena; Lusia Handayani (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2026)
The rapid growth of online gambling in Indonesia, marked by an 8,136.77% increase in transactions since 2018, highlights the urgent need for effective preventive communication targeting adolescents. This study aimed (1) to develop an illustrated story-based educational medium about online gambling and (2) to examine its effectiveness in improving adolescents’ knowledge and attitudes toward online gambling. A Research and Development (R&D) design was employed, combining expert validation of the media with a one-group pre-test–post-test experiment. Three experts in media design and online gambling content assessed the feasibility of the illustrated story using a validation questionnaire. Effectiveness testing involved 12 adolescents in Cilebut Village, Bogor, who completed knowledge and attitude questionnaires before and after exposure to the illustrated story. The results showed that the medium achieved an average expert validation score of 87.5%, indicating that it is feasible for educational use. Paired sample t-test analysis revealed a significant increase in knowledge scores from a mean of 6 to 9.16 (p = 0.001) and in attitude scores from 23.41 to 29.16 (p = 0.001) after the intervention. These findings conclude that illustrated story-based media is an effective tool to enhance adolescents’ knowledge and strengthen their attitudes against online gambling, and it holds promise for broader application in preventive education campaigns.